Tetrahedral Pegs in Square Holes: Stereochemistry of Diboron Porphyrazines and Phthalocyanines. (20th November 2018) - Tay, Aaron Chin Yit; Frogley, Benjamin J.; Ware, David C.; Conradie, Jeanet; Ghosh, Abhik; Brothers, Penelope J.
Abstract: The first examples of diboron complexes of the tetrapyrroles octaethylporphyrazine (OEPz) and 2, 9, 16, 23‐tetra‐t‐butyl‐phthalocyanine (Pc) are reported, counterpoints to the better known monoboron tripyrroles, subporphyrazine and subphthalocyanine. Two stereochemical possibilities are observed, with cisoid ‐B2 OF2 (OEPz), both cisoid ‐B2 OPh2 (OEPz) and transoid ‐B2 OPh2 (OEPz), transoid ‐B2 OF2 (Pc) and cisoid ‐B2 OPh2 (Pc) having been isolated and characterised, including structure determinations for the OEPz complexes. This variation in stereochemistry, which can be extended to include the previously reported transoid ‐B2 OF2 (porphyrin), cisoid ‐[B2 OF2 (corrole)] −, and both transoid ‐ and cisoid ‐B2 OF2 (calixphyrin), prompted a wider DFT study to elucidate the factors influencing the stereochemical preferences. This shows that the cisoid / transoid preference is correlated to the ease with which the macrocycle accommodates a rectangularly distorted N4 cavity.